Trends in Uveal Melanoma Presentation and Survival During Five Decades: A Nationwide Survey of 3898 Swedish Patients - Gill, Viktor; Herrspiegel, Christina; Sabazade, Shiva; Fili, Maria; Bergman, Louise; Damato, Bertil; Seregard, Stefan; Stålhammar, Gustav (Frontiers in Medicine, 2022)
Background In contrast to most other cancers, uveal melanoma (UM) is characterized by an absence of major improvements in patient survival during the last several decades. In this study, we examine changes in incidence rates, patient age and tumor size at diagnosis, treatment practices and survival for patients diagnosed in Sweden during the period 1960 to 2010. Methods All patients diagnosed with posterior UM between January 1st, 1960, and December 31st, 2009, in Sweden, were included (n=3898). Trends in incidence, primary treatment modality, patient age and tumor size were analyzed. Disease-specific survival was plotted in Kaplan-Meier curves and the cumulative incidence of UM-related mortality was evaluated in competing risk analysis. Results Crude (6.5 to 11.6 cases/million/year) and age-standardized incidence rates (5.6 to 9.6 cases/million/year) varied between individual years during the study period, but both had a stable linear trend overall (p≥0.12). Gradually, plaque brachytherapy with ruthenium-106 replaced enucleation as the most common primary treatment. The mean patient age at diagnosis increased from 59.8 years in 1960 to 66.0 in 2009. Conversely, the mean tumor size became gradually smaller during the period. In linear regression, the basal diameter and tumor apical thickness decreased with a slope coefficient of -0.3 (p=0.012) and -0.05 (p=1.2×10-5) per year after 1960, respectively. Patients diagnosed after 1990 had significantly better disease-specific survival than patients diagnosed before 1990 (p=7.1×10-13) Similarly, the cumulative incidence of UM-related mortality was highest for patients diagnosed 1960-1969 and 1970-1979, with slightly lower incidences for patients diagnosed 1980-1989 and even lower for those diagnosed after 1990 (p=7.1×10-13). The incidence of mortality from other causes than UM did not differ between periods (p=0.16). Conclusions In the period from 1960 to 2010, crude and age-standardized incidence rates of UM have remained stable in Sweden. Several other aspects have changed: Plaque brachytherapy with ruthenium-106 has replaced enucleation as the most common primary treatment modality; patients have become older and their tumors smaller at the time of diagnosis; and their survival has improved. This might indicate a beneficial survival effect of earlier diagnosis and treatment, but the potential influence from lead-time bias should be taken into consideration.